2022
DOI: 10.3390/plants11152018
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Cadmium and Nickel Toxicity and Phyto-Stimulation of Tomato Plant L. by Endophytic Micrococcus luteus and Enterobacter cloacae

Abstract: Cadmium (Cd) and nickel (Ni) are two of the most toxic metals, wreaking havoc on human health and agricultural output. Furthermore, high levels of Cd and Ni in the soil environment, particularly in the root zone, may slow plant development, resulting in lower plant biomass. On the other hand, endophytic bacteria offer great promise for reducing Cd and Ni. Moreover, they boost plants’ resistance to heavy metal stress. Different bacterium strains were isolated from tomato roots. These isolates were identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 104 publications
1
23
0
Order By: Relevance
“…These findings are consistent with other studies. In addition, the results demonstrated an increase in the use of azithromycin in 2020, consistent with other studies reporting increased use of azithromycin during the COVID-19 pandemic, especially in combination with hydroxychloroquine [26,32,[33][34][35]. This could be due to physicians' prior experience with azithromycin for respiratory infections, or it could be related to widespread off-label usage of azithromycin for the treatment of COVID-19 in other countries.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These findings are consistent with other studies. In addition, the results demonstrated an increase in the use of azithromycin in 2020, consistent with other studies reporting increased use of azithromycin during the COVID-19 pandemic, especially in combination with hydroxychloroquine [26,32,[33][34][35]. This could be due to physicians' prior experience with azithromycin for respiratory infections, or it could be related to widespread off-label usage of azithromycin for the treatment of COVID-19 in other countries.…”
Section: Discussionsupporting
confidence: 87%
“…This drop-in usage may be attributed to the increased use of other antibiotics such as azithromycin. However, other studies have reported a positive incremental change in third and fourth generation cephalosporin and lincosamide consumption [26][27][28][29][30]. This may be related to differences in race, variations in the most common infections, and the development of resistance in treated patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As the toxicity of mercury is increasing globally, it is critical to take serious action to limit its pollution and prevent its accumulation in highly consumed crops as wheat. Although several approaches, such as phytoremediation, soil remediation, and heavy-metal-resistant cultivars, may help to reduce heavy metal deposition in crops, their effectiveness is limited (Rizwan et al 2012;Badawy et al 2022). Hu et al (2020) found that synthesized or natural-sourced elicitors are highly effective approaches to minimizing heavy metal toxicity in plants.…”
Section: Introductionmentioning
confidence: 99%
“…An appropriate plant growth promoter is moringa leaf extract, which is rich in K, Ca, Fe, amino acids, carotenoids, phenols, ascorbate, and growth-regulating hormones (Basra et al, 2009;Ragaey et al, 2022). Plant defense against oxidative stress depends on antioxidants like ascorbic acid and glutathione, which are abundant in the chloroplasts of the moringa plant and other cellular compartments (Badawy et al, 2022;Sofy et al, 2021). According to Lee et al, (2008), the combined action of red and blue light may boost the accumulation of bioactive substances such as total polyphenols, anthocyanins, and flavonoids for all the antioxidant components thus tested.…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%